Introduction to the Special Issue of “Scientia et Fides” on Mariano Artigas - Santiago Collado (Scientia et Fides, 2016)
The occasion for the elaboration of this issue was the tenth anniversary of the death of Mariano Artigas, which took place on December 23, 2006. A period of ten years is a good excuse to do something allowed by the academic life though, paradoxically, not usually encouraged by its demands, namely, to take a moment to stop, to look back, and to think. I had the opportunity to work alongside Artigas during the last six years of his earthly life. Those years left a mark in me of which I am starting, I believe, to be conscious. In the contributions made in this issue, many of those who participated—who represented only a portion of those who desired to contribute but have unfortunately not been able to do so for many different reasons—manifest the footprint that knowing Artigas or reading his works has left not only in their academic life, but also in their personal life. [...]